ANALISIS ASPEK BIOFISIK DAN KIMIA PERAIRAN UNTUK PENGEMBANGAN BUDIDAYA TAMBAK DI WILAYAH PESISIR KECAMATAN PEDONGGA KABUPATEN PASANGKAYU SULAWESI BARAT - Mustainah Marsuki; Andi Tamsil; Ihsan Ihsan (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
In general, land use in Pasangkayu Regency is dominated by forests, both protected forests and production forests, plantations especially oil palm plantations, mixed gardens, rice fields both irrigated rice fields and rainfed rice fields, as well as shrubs, weeds, mangrove forests and wetlands, beaches, settlements, government buildings and other infrastructure facilities. This study aims to (1) Know the biophysical and chemical aspects of the waters, (2) Analyze the suitability of aquaculture land in supporting the development of aquaculture, and (3) Assess strategies for developing aquaculture ponds. The results showed that (1) the biophysical and chemical aspects of waters in coastal and marine areas, where coastal ecosystems, physical and chemical aspects ofthe waters strongly supported aquaculture activities, (2) the results of suitability of aquaculture land in the development of pond culture in Batu Oge Village Very suitable land with a land area of1,72 Ha, Adequate According to 61,07 Ha, and Appropriate 122,34 Ha. Malei village land suitability is quite suitable 16,47 ha, and according to 334,18 ha. Mertasari Village land suitability In accordance with the land area of 26,19 ha, and Village of land suitability in accordance with 2,27 ha of land area, and (3) Strategy for the development of pond culture in Pedongga District, Pasangkayu Regency, includes 3 strategies: technical meeting meeting between the local Fisheries Service with pond farmers to teach CBUB and CBIB, optimize the use of farm land, and determine the boundaries of the area for the development of ponds and oil palm.